Factors Causing Pending Claims at Nyi Ageng Serang Regional General Hospital - Rosmeida Marwah Utami; Savitri Citra Budi; Fendi Septiawan (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2023)
Nyi Ageng Serang Regional General Hospital submits monthly collective claims for the Social Health Insurance Administration Body patients. Based on the observations made at the Nyi Ageng Serang Regional General Hospital, the Social Health Insurance Administration Body claim file was pending by the Social Health Insurance Administration Body verifier because it needed to be confirmed. The pending claims will cause the payment of claims from the Social Health Insurance Administration Body to the hospital to be delayed, and it might affect service activities and financing for the hospital. Pending claims must be explored more deeply to the causal factors so they can be handled appropriately. This study aims to describe the factors causing pending claims for the Social Health Insurance Administration Body at the Nyi Ageng Serang Regional General Hospital. Data collection techniques used observation techniques, documentation studies, and interviews. Data analysis was performed using descriptive analysis. External factors that have caused pending claims include discrepancies in claim rates with the Minister of Health Regulations, incorrect codes, and incomplete codes. Meanwhile, the internal factors causing pending claims, according to the 5M management element, were the Man, Material, and Method factors.